A tervezés jellegzetességei civil szervezetekben - Szabados, György; Kulcsár, Gergely (Jelenkori Társadalmi és Gazdasági Folyamatok, 2010)
Managerial planning seems to be a vital function in the corporate activity. It is also va-lid for operating civic organizations, the activity of which highly increased in the trans-formed Hungarian Society. We have carried out questionnaire and deep interview survey to understand the planning practice of civic organization managers. We have realized that planning is a vital managerial function. In the sphere, long term planning is not possible, and the process is an internal affair of the organization itself. As a conclusion, we believe that organizations should open towards its environment and rely on a wider, professional expertise.